Representing Poverty and Attacking Representations: Some Anthropological Perspectives on Poverty in Development. - Green, M (GPRG, 2005)
This article explores some aspects of the representation poverty in development studies from an anthropological perspective. Starting from the history of the category of poverty as the central target for development policy, the article shows how the ways in which poverty is assessed not only have implications for the kinds of strategies adopted to address it but for theories about its causes. Such accounts underplay the significance of social relations in contributing to poverty outcomes and the political structures which keep people poor. Anthropological approaches to the study of deprivation and inequality can provide a useful corrective to the homogenising effects of development perspectives on poverty.